Lignocellulosic biomass from agricultural waste to the circular economy: a review with focus on biofuels, biocomposites and bioplastics - Mujtaba, Muhammad; Fernandes Fraceto, Leonardo [UNESP]; Fazeli, Mahyar; Mukherjee, Sritama; Savassa, Susilaine Maira [UNESP]; Araujo de Medeiros, Gerson [UNESP]; do Espírito Santo Pereira, Anderson [UNESP]; Mancini, Sandro Donnini [UNESP]; Lipponen, Juha; Vilaplana, Francisco (Elsevier, 2023)
Industries are working to minimize their reliance on petrochemicals and petroleum-based industrial components and replace them with biobased, sustainable, and environmentally friendly alternatives due to the global warming emergency caused by the uncontrolled production of greenhouse gases. The agricultural waste provides large volumes of lignocellulosic biomass, a sustainable resource material to develop a wide portfolio of bioproducts. Recent developments in integrated biorefineries have enhanced the utilization of waste lignocellulose components to generate biofuels, platform chemicals, resins, bioplastics, additives, and other biobased materials for a variety of applications. Here in this review, we have summarized recent advancements in the processing of lignocellulosic biomass from agricultural waste. Additionally, this review thoroughly discussed the recent technological advancements in the utilization of various lignocellulose biomass constituents for biofuels, biocomposites, and bioplastics. Finally, an assessment of the currently existing literature gaps and prospective future perspectives for the development of lignocellulosic biomass from agricultural waste has been conducted.
Keywords: Biofuels; Bioplastics; Biorefineries; Sustainability